English Teacher Strategies in Motivating Low-Achiever Students - Adinda Wahyu Budiyanti; Annur Rofiq; Musli Ariani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to explore how English teachers can effectively motivate low-achieving students through various strategies identified during classroom observations. The research highlights that teachers establish foundational motivational conditions by starting lessons enthusiastically and fostering personal connections with students, which encourages them to try harder and believe in their abilities. Additionally, by emphasizing the importance of learning English and offering bonus scores, teachers generate initial motivation that can improve low-achieving students' grades. To maintain this motivation, teachers provide opportunities for students to present their learning outcomes, enhancing their engagement and confidence. Furthermore, helping low-achieving students improve their pronunciation encourages positive self-evaluation, making them feel valued and motivated to continue learning. The findings suggest that it is essential for teachers to implement effective motivational strategies in order to facilitate better understanding and learning among their students. Therefore, an English teacher must possess both effective strategies and enthusiasm to motivate students and ensure their comprehension of the lesson.